Identificación de Aislados de Cryptococcus neoformans Usando Agar Staib sin Creatinina - Vanessa Nardelli; Celina Pérez; Sofía Mata-Essayag; María Teresa Colella; Arantza Roselló; Claudia Hartung de Capriles; María Eugenia Landaeta; Carolina Olaizola; Sylvia Magaldi (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
In mycology, culture is the best way to demonstrate and identify pathogenic fungi. Many kinds of media have been developed and modified, using fungal biochemical properties to recognize them. The most common media are Sabouraud, Malt Agar, Cornmeal agar, Potato-dextrose agar, and Staib agar. Staib agar has been widely used for identification of yeasts from the genus Cryptococcus and other fungi. The aim of this study was to demonstrate the usefulness of Staib agar, and of a modified Staib medium without creatinine, in the isolation and identification of fungi. Forty-six Cryptococcus neoformans strains plus one control strain were identified by morphological and  biochemical criteria, using urease test (Christensen urea agar) and culture in Sablac medium. The strains were then transferred into standard Staib and Staib without creatinine agar plates. Morphological features and phenoloxidase production were evaluated after one week incubation at room temperature (26-28°C). Culture in standard and modified Staib agar yielded brown color colonies (phenoloxidase production) in both media in 43 (91.5%) cases. Staib agar without creatinine is an excellent medium for identification of C. neoformans, with the advantage of a low cost and easy preparation.